STUDY OF BEHAVIOUR-BASED NAVIGATION FOR INDOOR MOBILE ROBOT - Khalid, Abdullah (Universiti Teknologi PETRONAS, 2020)
An indoor mobile robot having autonomous navigation can move along unknown path by using sensors input in an indoor environment. In this project, we are studying algorithms for beahviour-based navigation in a maze-like structure in an indoor environment where robot will move from point A to point B in the maze autonomously. We are studying three beahviours for autonomous navigation systems namely; Wall following, Obstacle avoidance and Goal seeking. We are building Arduino based robot with Ultrasonic sensors. When autonomously driven, it will be capable of detecting obstacles and finding its on way to move towards the goal. In the next phase of the project, we will be building indoor mobile robot by installation of all components, designing of beahviour-based algorithms, circuit designing, several rounds of testing in indoor maze-like structure to study three selected beahviours of autonomous navigation.